The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1186/s12909-023-04053-2
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional simulation of acute care for nursing and medical students: interprofessional competencies and transfer to the workplace

Abstract: Background Teamwork and communication are essential tools for doctors, nurses and other team members in the management of critically ill patients. Early interprofessional education during study, using acute care simulation, may improve teamwork and communication between interprofessional team members on the long run. Methods A comparative sequential quantitative–qualitative study was used to understand interprofessional learning outcomes in nursing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…133,[135][136][137] Learners also reported higher self-efficacy and satisfaction with interprofessional training. 133,134,138 These results were not ubiquitous as some studies did not reveal any differences in learning outcomes. 134,138 Harms and burden: No harm or negative impacts were reported following the implementation of interprofessional training, and no studies reported on financial impacts.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…133,[135][136][137] Learners also reported higher self-efficacy and satisfaction with interprofessional training. 133,134,138 These results were not ubiquitous as some studies did not reveal any differences in learning outcomes. 134,138 Harms and burden: No harm or negative impacts were reported following the implementation of interprofessional training, and no studies reported on financial impacts.…”
Section: Discussionmentioning
confidence: 92%
“…Summary of the evidence: Six studies comparing interprofessional vs single-professional team training of healthcare students [133][134][135][136][137][138] were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation